National monuments and public access: Towards statistical data on cultural heritage - Macedo, S.C.; Neves, J. S.; Santos, J.; Lima, M. J. (17th International Conference on Arts and Cultural Management (AIMAC), 2024)
Despite expectations for built cultural heritage, Portugal still lacks a system for measuring the uses of heritage and inform development strategies. Efforts in heritage qualification drift towards conservation and restoration but do not include information on national and foreign visitors. One of the main causes lies on recurring argument of CH vastness, heterogeneity and access regime, but also on the legal framework that does not refer the production of statistical data, in spite the existing parallels on museums. Heritage fruition is a low studied subject and together with the absence of systematically collected data, the heritage frame lacks information for its assessment and impacts. The national Survey of National Monuments (IMNP) occurs within the study From Safeguard to Valorization: the National Monuments of Portugal and public access and aims at the production of systematic data on built cultural heritage, classified under the category National Monuments, that contributes to a statistical heritage project of a national scope.